Intercultural Communication Based on the Perspective of the Effects of Cultural Shock and Labeling on Self-Disclosure and Self-Confidence of Acehnese Students in Malang - Juhra, Muhammad Anshar; Pohan, Syafruddin; Nurbani, Nurbani (EduLine: Journal of Education and Learning Innovation, 2025)
This research is based on the reality that Acehnese students staying in Malang often experience the phenomenon of cultural shock and negative labeling during their studies in Malang. The negative labeling they have received such as “ Aceh pungo, marijuana dealers, members of the Free Aceh Movement (GAM)”. This labeling causes the lack of self-disclosure and lack of confidence of Acehnese students in their communication in Malang. This research aims to analyze the effects of cultural shock and negative labeling on self-disclosure and self-confidence of Acehnese students in their communication process in Malang. The research uses Winkelmann’s cultural shock theory and Edwin E. Lemert’s labeling theory. Utilizing a quantitative approach and a correlational method, the research targets members of IPPMA, comprising a population of 133 individuals. A sample size of 100 respondents was determined using the Slovin formula. The data are collacted by distributing questionnaires to respondents. After the data obtained, they are sequenced and analyzed using multiple regression analysis. The results indicate that cultural shock affects self-disclosure and self-confidence, while negative labeling does not affect self-disclosure and self-confidence. The simultaneous testing indicates that the combined effect of cultural shock and negative labeling on self-disclosure and self-confidence is weak.